The role of the ultrasound examination of the brachial plexus in thoracic outlet syndrome - D. S. Druzhinin; S. S. Nikitin; L. M. Boriskina; E. S. Druzhinina; M. L. Novikov; A. A. Eliseeva (Нервно-мышечные болезни, 2020)
Introduction. Difficulties in determining the compression of the neurovascular bundle with the thoracic outlet syndrome raises the question of finding an accessible and reproducible method for the neuroimaging of the brachial plexus and surrounding tissues.Purpose of the study – to develop an ultrasound diagnostic algorithm using a stress test to determine the level and cause of brachial plexus compression in comparison with the results of a clinical assessment.Materials and methods. 111 patients with verified compression of the brachial plexus at the level of the interstitial (65.7 %) and bone-clavicular space (21.6 %), as well as the tendon of the pectoralis minor muscle (12.6 %) were examined. The study protocol including the Adson ultrasound stress test, the assessment of the lower trunk in the interstitial space, and the test with ultrasound evaluation of the axillary artery at the level of the tendon of the pectoralis minor muscle with passive abduction of the arm back and up was used.Conclusion. An ultrasound study of the brachial plexus demonstrated informativeness in assessing the level and possible cause of compression, which opens up the possibility of using the method in routine neurological practice.